2020
DOI: 10.3390/s20040966
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Children with ASD and Their Parents: Design of a Serious Game for Anxiety and Stress Reduction

Abstract: Autism Spectrum Disorder (ASD) is characterized by social interaction difficulties and communication difficulties. Moreover, children with ASD often suffer from other co-morbidities, such as anxiety and depression. Finding appropriate treatment can be difficult as symptoms of ASD and co-morbidities often overlap. Due to these challenges, parents of children with ASD often suffer from higher levels of stress. This research aims to investigate the feasibility of empowering children with ASD and their parents thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 72 publications
(127 reference statements)
2
43
0
Order By: Relevance
“…In fact, lower levels of stress were found in students after the implementation of team sport and dance activities [71]. Active games also seem to have a role in the reduction of stress and anxiety among children with psychological issues [72] and alienation experiences [73], and even in adults [74]. In line with these and our study, Yogman [75] confirms that games are effective antidotes to reduce youth's aggression and uncontrolled emotion generated by toxic stress.…”
Section: Psychological Healthsupporting
confidence: 85%
“…In fact, lower levels of stress were found in students after the implementation of team sport and dance activities [71]. Active games also seem to have a role in the reduction of stress and anxiety among children with psychological issues [72] and alienation experiences [73], and even in adults [74]. In line with these and our study, Yogman [75] confirms that games are effective antidotes to reduce youth's aggression and uncontrolled emotion generated by toxic stress.…”
Section: Psychological Healthsupporting
confidence: 85%
“…One of the premises supported by almost all the literature is the need for customisation of technology [18,22,32,33,35,37,[39][40][41][42][44][45][46][47][48][49]. In this study, the elements identified as customisable for each child were images, sound, reinforcement, text, colours, screen layout and presentation, and content.…”
Section: Discussionmentioning
confidence: 98%
“…The need to involve children with ASD, family members and professional interdisciplinary team members in the design of technology emerged from interviews and observations, as previously described in several publications [22,33,38,42,[46][47][48][49]. Several authors have implemented studies to capture the perspectives on technology design of end-users and stakeholders in participatory design from a qualitative or mixed approach [22,41,42,[44][45][46]49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These games incorporate physical activity in the gameplay and can be used for different purposes such as physical activity encouragement [ 30 - 33 ] or rehabilitation to recover from brain injuries, cognitive impairments [ 34 ], or motor deficiencies [ 35 , 36 ]. Finally, with respect to the games that influence health precursors, some examples are games that reduce stress and anxiety [ 37 ], deal with depression [ 38 ], or prepare for cancer treatments [ 39 ]. The game proposed in this paper can be classified as a game designed for nonexpert users to increase their knowledge on a health topic, particularly on first-aid survival techniques.…”
Section: Introductionmentioning
confidence: 99%